COVID-19: management focus of reopened tourist destinations - Li, Zhiyong; Zhao, Qingxue; Huo, Tingting; Shao, Yuhong; Hu, Zhongyi (Current issues in tourism, 2022)
Reopen major tourist destinations is one of the significant recovery initiatives for the tourism industry after the outbreak of crises. However, few studies have focused on management measures during the reopening of tourist destinations. In this regard, this study adopts the co-word analysis to map the topics of 273 notices of the reopened national 5A scenic areas in China. The key themes are identified including (i) prevention measures, (ii) business scope, (iii) rules for tourists and (iv) preferential measures. Moreover, the management focus varies between natural and cultural destinations. This study provides suggestions for research on epidemic-induced crisis management in tourism.